Multimodality imaging of scimitar syndrome in adults: A report of four cases. Issue 10 (23rd August 2018) - Ngai, Calvin; Freedberg, Robin S.; Latson, Larry; Argilla, Michael; Benenstein, Ricardo J.; Vainrib, Alan F.; Donnino, Robert; Saric, Muhamed
Abstract : Partial anomalous pulmonary venous return (PAPVR) comprises a group of congenital cardiovascular anomalies associated with pulmonary venous flow directly or indirectly into the right atrium. Scimitar syndrome is a variant of PAPVR in which the right lung is drained by right pulmonary veins connected anomalously to the inferior vena cava. Surgery is the definitive treatment for scimitar syndrome. However, it is not always necessary as many patients are asymptomatic, have small left‐to‐right shunts, and enjoy a normal life expectancy without surgery. We report multimodality imaging in four adults with scimitar syndrome and the implications for management of this rare syndrome.